MENDENGAR SEBAGAI SALAH SATU ALAT KOMUNIKASI - Dewi, Yuni Retna (Universitas Prof. Dr. Moestopo (Beragama), 2007)
Surveys indicate managerial people in organizations spend up to 80 percent of their workday in toceto face conversations, in meetings, on the phone, or writing, other research has suggested that approximately 60 percent of the workday to spent listening, yet the estimates are that less than 50 percent of the area messaged used in a day are fully understood. A recent survey of Australia business executives showed that the ability to listen was ranks as the most important communications skill necessary for persona/- success in the organizations. Similar results were obtained in a 1982. Study after communication skills Australian accounting raduates. The purpose of this writing is to increase awareness of how much of our day was spent listening, to identify some of the major barriers of effective listening, and finally to learn how to concentration, objectivity, questioning and feedback can improve listening behavior. Listening is the communication channel we use most frequently. Yet surveys show that listening skills are the least developed !.